Lúpulo em nova perspectiva: da bebida milenar ao conservante natural de alimentos - Rodrigues, José Eduardo Coelho (Universidade Federal de São Carlos, 2025)
The growing appreciation for natural and safe foods, together with the global effort to reduce losses and waste, has encouraged the search for alternatives to synthetic preservatives. In this context, hops (Humulus lupulus), known for their use in beer production, have attracted interest as a source of bioactive compounds with recognized antimicrobial and antioxidant potential. This review, with an emphasis on publications from 2019 to 2025, investigated the use of hops in food preservation. Among the main identified compounds are α- and β-acids, polyphenols, and essential oils, whose antimicrobial action involves processes such as cell membrane disruption, cytosol acidification, ionic imbalance, and leakage of intracellular components. These compounds showed greater effects against Gram-positive bacteria, such as Listeria monocytogenes, Staphylococcus aureus, Enterococcus faecalis, and Leuconostoc gelidum, as well as yeasts like Candida albicans. In contrast, Gram-negative microorganisms such as Escherichia coli and species from the Enterobacteriaceae family proved more resistant. The antimicrobial efficiency of hops depends on factors such as pH, food matrix composition, lipid content, and extraction method, being enhanced in acidic environments and reduced in high-fat foods. Studies report relevant results in matrices such as cheeses, meats, juices, and fermented products, where hops contributed to reducing microbial load and delaying oxidation while maintaining sensory quality and exhibiting combined antioxidant and antimicrobial activity. Their incorporation into foods aligns with the clean label concept, enabling the replacement of artificial preservatives with natural ingredients recognized by consumers. Despite the advances, challenges remain related to selectivity against microorganisms, chemical variability of extracts, and the lack of standardization in application methods. Therefore, hops represent a natural, efficient, and sustainable alternative to synthetic preservatives, with the potential to extend food shelf life and promote the development of safer products aligned with modern consumer expectations.
Hops in a new perspective: from an ancient beverage to a natural food preservative.
Keywords: Compostos antimicrobianos; Antioxidante; α-ácidos; β-ácidos; Antimicrobial compounds; Antioxidant; α-acids; β-acids; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::QUIMICA, FISICA, FISICO-QUIMICA E BIOQUIMICA DOS ALIM. E DAS MAT.-PRIMAS ALIMENTARES; 3. Saúde e Bem-Estar; 2. Fome Zero e Agricultura Sustentável